Non-existence of causal, standard classical electrodynamics with point charged particle - Zin, Paweł (Journal of physics. A, Mathematical and theoretical, 2024)
The existence of consistent, standard and causal theory of point charged particle (for example electron) interacting with electromagnetic field was the subject of many investigations. This problem is often stated as the description of the system of electromagnetic pulse of radiation interacting with single point charged particle (for example electron). The correct theory should give the causal particle trajectory for any electromagnetic pulse of radiation. Up to now no such theory was formulated. We show that for certain electromagnetic pulse of radiation and point particle being initially at rest, there does not exist a causal and physical particle trajectory that satisfies energy and momentum conservation. This shows that the causal, standard electrodynamics of scalar point particles, valid for all possible external pulses, does not exist.